Implementation of Exponential Smoothing in Forecasting the Export Value Price of Oil and Gas in Indonesia - Ansari Saleh Ahmar; Abdul Rahman; Sitti Masyitah Meliyana R.; Rusli Rusli; Nachnoer Arss; Alok Kumar Panday (PT Mattawang Mediatama Solution, 2023)
This study aims to predict the value of oil and gas export prices in Indonesia using exponential smoothing. Exponential smoothing was applied because the data analysis revealed that the data consisted of trends and seasonal components. This study uses secondary data obtained from the website of the Central Bureau of Statistics of the Republic of Indonesia, covering the value of oil and gas exports in Indonesia every month from January 2010 to March 2022. The study obtained the exponential smoothing parameters, including α = 0.5153984, β = 0.06410119, and g = 0.7137603, with a seasonal length of L = 12. The forecast for the next five periods in millions of US: April 2022 (1111.765), May 2022 (1250.465), June 2022 (1405.016), July 2022 (1447.510), and August 2022 (1452.984).